Fundamentals of entrepreneurship (ENT300) Business plan: Cleaning & sanitize service by ANDA / Amir Syauki Zaihaliraya … [et al.] - Zaihaliraya, Amir Syauki; Muhammad @ Ibrahim, Muhammad Nazren Aiman; Mustahna, Muhammad Danish Haiqal; Baharudin, Muhammad Amar Firdaus (2021)
ANDA Corporation is a start-up organization based in Kuantan, Pahang. ANDA Corporation is a company that provides cleaning services for high-end residential houses. We are an organization that offers professional, trustworthy and also effective service to help in growing the business quickly. From the outset, ANDA Corporation has its own objectives that is quite ambitious. The first thing is to always exceeds our customer’s expectations. By doing so, their satisfaction is guaranteed and will ensure repeat business also word of mouth referrals. Increasing our client base by 20% is our second objective. Achieve a sustainability of cash by the end of year one is the third objective. The last objective is to have 30% conversion rate of prospective customers into clients. The Market Even though the competition in the residential cleaning industry is plenty, there are a few competitors that are considered professional and trustworthy. ANDA Corporation will target two distinct market segments to go after, two income and one-income wealthy families. The affluent single income households are growing at 11% while the two income families are growing at a slightly faster rate which is 13%. Services Offered As mentioned earlier, ANDA Corporation is a residential household cleaning service. We are able to handle all kinds of possible residential needs, from general house cleaning to child and pet disasters. All of our services are offered in the most professional manner possible. Professionalism, trustworthiness and effectiveness are ANDA Corporation’s spell in order to have a good business. By having these kind of spells, customers will feel at ease with ANDA Corporation immediately. This is indicated by the fact it is not uncommon for clients, after their first appointment, to provide ANDA Corporation with house keys so they may come unattended at their leisure time to provide future services. Management With years in the industry, a group of four, Amir, Nazren, Amar and Danish, (ANDA), have decided to form a partnership to take a chance at opening their own business in the industry that they have so much knowledge and experience. The four of them initially spent years at Sanitation Management, a nationwide cleaning service. They then moved onto Immaculate Cleanception where they received ample management training. It was these experiences that gave them the skills and confidence to join hands to open up their own business. ANDA Corporation is an exciting opportunity that combines the skills and passion of the principal with an unmet need in Kuantan, Pahang. Profit margins will be 1.4% in year 1 and 14.7% in year three. ANDA Corporation will generate over RM188,000 in sales by the end of year one and RM228,000 by the end of year three.